Genomic insights into runs of homozygosity, effective population size and selection signatures in Iranian meat and dairy sheep breeds - Zohre Yousefi; Mohammad Hossein Moradi; Mohammad Taghi Beige-Nasiri; Masoud Shirali; Rostam Abdollahi-Arpanahi (PLoS ONE, 2025)
Genome-wide scan for run of homozygosity (ROH) stretches, effective population size (Ne) and selection signatures can help to elucidate mechanisms of selection and pinpoint genomic regions linked with phenotypic traits. This study aimed to identify the genomic patterns of ROH, Ne and selection signatures in two Iranian main sheep breeds including Afshari and Qezel (known as meat and dairy sheep, respectively) using 49,017 single nucleotide polymorphisms (SNPs) generated using the ovine 50K SNP BeadChips. Analysis of ROH in Iranian sheep breeds revealed the differences in the pattern of ROH length and burden in these breeds. Inbreeding estimated based on ROH stretches showed very low amount of inbreeding in these indigenous sheep breeds. The Qezel breed displayed a higher Ne than Afshari breed. Furthermore, the potential selection was detected in genomic regions using three complementary approaches including FST (fixation index), XP-EHH (cross-population extended haplotype homozygosity), and hapFLK (haplotype differentiation). Our results identified the genomic regions that were enriched with the genes associated with immune response (e.g., IL23A, STAT2 and DOCK5), milk traits (e.g., PCCA, ACAP3, TTK and BTG3), energy metabolisms (e.g., GLS2), reproduction (e.g., ANGPT2), fecundity (e.g., BMP5), nervous system (e.g., DLG2, PCDH9, and FRMPD4), growth traits and muscle formation (NPY, MYF5 and PPP1R12A), and sweat gland development (SCNN1D). Some regions were also detected for the first time and overlapped with no genes suggesting novel loci associated with traits that differentiate these breeds. Overall, the finding of this study may shed light on the genomic regions linked to economically important traits in sheep as well as for developing the conservation and selection breeding programs.